1999
DOI: 10.4319/lo.1999.44.2.0282
|View full text |Cite
|
Sign up to set email alerts
|

Origins and scale dependence of temporal variability in the transparency of Lake Tahoe, California–Nevada

Abstract: Secchi depth has been measured in Lake Tahoe an average of every 12 d since July 1967. Because of the unusual clarity of the lake, Secchi depth measurement is responsive to small changes in light-attenuating particles, and the record exhibits strong variability at the seasonal, interannual, and decadal scales. Using recently developed methods of applied time-series analysis, the mechanisms of change were delineated at each scale. The seasonal pattern is a bimodal one, with two minima at approximately June and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 42 publications
3
85
0
1
Order By: Relevance
“…This impact is greatest in years following heavy stream runoff, and is prolonged by an absence of deep-water mixing events (Jassby et al 1999). Following mixing, the fine particles suspended at the upper layer are dispersed throughout the water column.…”
Section: Possible Effects On Lake Due To Warming Trendmentioning
confidence: 99%
“…This impact is greatest in years following heavy stream runoff, and is prolonged by an absence of deep-water mixing events (Jassby et al 1999). Following mixing, the fine particles suspended at the upper layer are dispersed throughout the water column.…”
Section: Possible Effects On Lake Due To Warming Trendmentioning
confidence: 99%
“…The former is influenced by the timing of snowmelt and storm runoff, and by the suspended sediment concentration, and the latter by the seasonal cycle of warming, stratification and mixing. Additional modeling may help to sort out the interaction between stream runoff, lake thermal structure and water clarity, but it seems likely that increased inflow of fine sediment (from more intense rainfall, drought and wildfires) will interact with increasing thermal stability to prolong the period of reduced water clarity that follows periods of heavy runoff (Jassby et al 1999). …”
Section: Role Of the Pdo And Ensomentioning
confidence: 99%
“…In earlier synoptic studies of lake primary productivity, Goldman found the Index Station to represent whole lake conditions (Goldman 1974). Scientific data shows that Secchi depth is directly related to the amount of suspended matter in the water (Jassby et al 1999). This suspended matter is composed of both biotic materials and suspended inorganic silt or sediment Extensive research on the spatial distribution of free-floating algae indicates a marked correspondence between the highest algal growth rates and the most extensive shoreline development.…”
Section: Changing Water Qualitymentioning
confidence: 99%
“…Most commonly, clarity is expressed as a Secchi depth: the depth at which an eight-inch white disk is no longer visible from the surface as it is lowered into a waterbody. Regular measurements at the UC Davis/Tahoe Research Group Index Station began in 1967 and have been made on average every 12.2 days since then (Jassby et al 1999). In earlier synoptic studies of lake primary productivity, Goldman found the Index Station to represent whole lake conditions (Goldman 1974).…”
Section: Changing Water Qualitymentioning
confidence: 99%
See 1 more Smart Citation